Properties of the simian virus 40 (SV40) large T antigens encoded by SV40 mutants with deletions in gene A. - Cole, C N (1986)
The biochemical properties of the large T antigens encoded by simian virus 40 (SV40) mutants with deletions at DdeI sites in the SV40 A gene were determined. Mutant large T antigens containing only the first 138 to 140 amino acids were unable to bind to the SV40 origin of DNA replication as were large T antigens containing at their COOH termini 96 or 97 amino acids encoded by the long open reading frame located between 0.22 and 0.165 map units (m.u.). All other mutant large T antigens were able to bind to the SV40 origin of replication. Mutants with in-phase deletions at 0.288 and 0.243 m.u. lacked ATPase activity, but ATPase activity was normal in mutants lacking origin-binding activity. The 627-amino acid large T antigen encoded by dlA2465, with a deletion at 0.219 m.u., was the smallest large T antigen displaying ATPase activity. Mutant large T antigens with the alternate 96- or 97-amino acid COOH terminus also lacked ATPase activity. All mutant large T antigens were found in the nuclei of infected cells; a small amount of large T with the alternate COOH terminus was also located in the cytoplasm. Mutant dlA2465 belonged to the same class of mutants as dlA2459. It was unable to form plaques on CV-1p cells at 37 or 32 degrees C but could form plaques on BSC-1 monolayers at 37 degrees C but not at 32 degrees C. It was positive for viral DNA replication and showed intracistronic complementation with any group A mutant whose large T antigen contained a normal carboxyl terminus. These findings and those of others suggest that both DNA binding and ATPase activity are required for the viral DNA replication function of large T antigen, that these two activities must be located on the same T antigen monomer, and that these two activities are performed by distinct domains of the polypeptide. These domains are distinct and separable from the domain affected by the mutation of dlA2465 and indicate that SV40 large T antigen is made up of at least three separate functional domains.